Understanding of Flower Initiation Pattern and Developmental Stages of Epiphyte orchid Aerides odorata Lour., from Sabah - Nor Amirah Shamsudin,; Jualang Azlan Gansau,; Ahmad Asnawi Mus,; Heira Vanessa Nelson,; Devina David,; Nor Azizun Rusdi, (Tropical Life Sciences Research, 2026)
Aerides odorata Lour. is an epiphytic orchid with commercial potential due to its intriguing flowers. Nevertheless, the flowering patterns of this species have not been investigated. Flower initiation and development are important for plant reproduction because they mark the transition from vegetative growth to reproductive growth, allowing plants to produce flowers and ultimately, seeds or fruits. Besides, floral initiation and development in orchids differ among various species. This work seeks to observe and document the flowering stages and find the optimal maturity stage for Aerides odorata Lour seed pod, which is crucial for in vitro asymbiotic seed germination. Three orchid plants with 2–3 peduncles each were observed daily over five months, every morning (9:00 a.m.–11:00 a.m.) to record development from spike initiation to full bloom, and subsequently for three months post-pollination until capsule dehiscence. Summarising the information on floral developmental stages involved four main phases: spike formation (considered the first day of the phases), bud initiation, flowering and senescence until seed pod formation. The results showed that approximately twelve significant floral developmental stages were systematically documented, each correlated with time intervals and morphological landmarks. Upon observation, it was noted that each of these species could create a maximum of 22 flower buds per plant. The flower is fully wilted 85 days after being pollinated. In addition, the pollinated flowers transformed into capsules and fully reached maturity after 100 days following pollination. Gaining insight into the floral initiation process in orchid species is crucial for optimising cultivation conditions and promoting successful flowering in these aesthetically pleasing and varied plants.